Techniques of theatrical presentation and its work in heterogeneous places - شيماء حسين طاهر د. (lark, 2020)
The concept of heterotherapy (heterogeneous places) resulted from the fact that a modern term was first used by the philosopher Michel Foucault, whose purpose was to present places that contrasted with each other and contradicted them and to announce the stand of utopia, which included ideal philosophy and later came until the advent of material philosophy, but Foucault did not announce the death But did work to find alternative to the city or place that is present in the minds of idealists did not become a reality, until the Htrotopia to announce the existence of an ideal place already exist and was fictional, but its presence is located in the place, where the place is linked to other places Whiten Spend it, it is several The place and not’s locations one place according to the mechanism of the appearance of a place at the expense of another place be of active identity more than the previous place. The research included four chapters, the first of which included the research problem of the following question: How can the techniques of theatrical presentation in the formation and highlighting heterogeneous places and contrast and different according to the concept of heterophobia? The second chapter, which included the theoretical framework and be of two subjects, the first interest is studied by heterogeneous places and their technical formations in the world theatre The current research aims at how the techniques of heterogeneous places and their technical structures can be used in the Iraqi theater, The chapter concluded with the indicators that emerged from the theoretical framework. The chapter included the "Limits of Search" which will determine the dates of 2013 and the venue of the theater performances presented in Baghdad The chapter concludes with the definition of terms The second chapter deals with the theoretical framework and is composed of two subjects. . The first one deals with the heterogeneous places and their technical structures in the world stage. The second topic is the study of heterogeneous places and their technical structures in the Iraqi theater. The chapter concluded with the indicators that resulted from the theoretical framework While the third chapter included the research procedures of the sample of research and research tools within the descriptive analytical approach, to come the analysis of theatrical play (Dreams Carton), while the fourth chapter came with results, which was the most prominent; . 1-The technique works to give the recipient the possibility of a heterogeneous form, through which the presentation and its aesthetics and granting its spaces. . 2 - The techniques contribute to the granting of heterogeneous places through which the presentation and its aesthetics in the creation of interpretative spaces for the presentation of each space marks the space of assumption and space metaphor and the space of the presentation